The Antioxidant and Antimicrobial Activities of Cornsilk Extract Encapsulated in Polysaccharide Nanoparticles - Mady, Maryam (AUC Knowledge Fountain, 2021)
Corn silk possess antibacterial and antioxidant activities due to its phenolic compounds but they are of low bioavailability that requires some innovative techniques to develop such active ingredients in a safe and less toxic manner. Accordingly, silk extract SE was encapsulated in chitosan nanoparticles CS NPs, which is a natural and abundant polymer derived from chitin. Among 15 experimental trials via design expert software, the optimum formula of SE x\CS NPs was prepared at 800 rpm, 5hrs. on magnetic stirrer, and by CS: TPP ratio was 2.5:1. Then SEM showed the majority of particles size diameter in the range of 25, 37, 39, and 55 and 77 nm were confirmatory for DLS particle size measurements of SE 0.5\CS NPs, SE 1\CS NPs, SE 1.5\CS NPs, and SE 2\CS NPs. FTIR results were confirmed the successful encapsulation and of SE in CS NPs by the appearance of the aromatic group bands at the wavenumber 1577.9 and 1417.5 cm-1. The cumulative extract release percentage was compared in two PH media showing no difference in their release profile. The release behavior of SE from CS NPs in those PH was indicative for using SE x\CS NPs as a topical preparation. SE x\CS NPs were tested for their antioxidant activities where % inhibition (free radical scavenging activity) of the four preparations SE 0.5\CS NPs, SE 1\CS NPs, SE 1.5\CS NPs, and SE 2\CS NPs showed 83.7, 84.7, 87.4, and 95.4% respectively higher than their corresponding amounts of free extract 31.5, 61.1, 74, and 87.4%. The TPC assay showed much lesser results for the four preparations of SE x\CS NPs ranged from 2.6 to 3.7 mg GAE\gm sample than that of their corresponding amounts of free extract which ranged from 16.5 to 35.7 mg GAE\gm sample. Also, the decreased values of TPC was indicative for the successful encapsulation of SE. The antibacterial test against S.auerus showed 100% BGI. In contrary, the antibacterial test against E.coli for the four preparations SE 0.5\CS NPs, SE 1\CS NPs, SE 1.5\CS NPs, and SE 2\CS NPs showed 70.44, 76.10, 82.51, and 98.27% BGI which was higher than that of their corresponding amounts of free extract 40.11, 59.30, 73.40, and 84.01% BGI.